Insulin in motion: The A6-A11 disulfide bond allosterically modulates structural transitions required for insulin activity. Issue 1 (December 2017) - van Lierop, Bianca; Ong, Shee; Belgi, Alessia; Delaine, Carlie; Andrikopoulos, Sofianos; Haworth, Naomi; Menting, John; Lawrence, Michael; Robinson, Andrea; Forbes, Briony
Abstract The structural transitions required for insulin to activate its receptor and initiate regulation of glucose homeostasis are only partly understood. Here, using ring-closing metathesis, we substitute the A6-A11 disulfide bond of insulin with a rigid, non-reducible dicarba linkage, yielding two distinct stereo-isomers (cis andtrans ). Remarkably, only thecis isomer displays full insulin potency, rapidly lowering blood glucose in mice (even under insulin-resistant conditions). It also posseses reduced mitogenic activityin vitro . Further biophysical, crystallographic and molecular-dynamics analyses reveal that the A6-A11 bond configuration directly affects the conformational flexibility of insulin A-chainN -terminal helix, dictating insulin's ability to engage its receptor. We reveal that in native insulin, contraction of the Cα -Cα distance of the flexible A6-A11 cystine allows the A-chainN -terminal helix to unwind to a conformation that allows receptor engagement. This motion is also permitted in thecis isomer, with its shorter Cα -Cα distance, but prevented in the extendedtrans analogue. These findings thus illuminate for the first time the allosteric role of the A6-A11 bond in mediating the transition of the hormone to an active conformation, significantly advancing our understanding of insulin action and opening up new avenues for the design of improved therapeutic analogues.